One Health Approach to Environmental and Public Health Challenges: Bridging the Gap between Human, Animal, and Environmental Health - Benny Novico Zani; Jackson Lee; Muntasir Muntasir (Yayasan Adra Karima Hubbi, 2026)
Background. This study is grounded in the growing recognition that complex environmental and public health challenges cannot be effectively addressed through sectoral approaches that separate human, animal, and environmental health. Accelerating climate change, biodiversity loss, emerging zoonotic diseases, and environmental degradation have intensified interactions across these domains, revealing critical weaknesses in fragmented health governance. Purpose. The objective of this research is to examine how the One Health approach can serve as an integrated framework to bridge disciplinary and institutional gaps in addressing contemporary environmental and public health challenges. Method. The study employs a qualitative integrative review design, synthesizing evidence from peer-reviewed international journals, policy reports, and global health frameworks to identify patterns, mechanisms, and implementation strategies associated with One Health practices. Results. The findings indicate that One Health-oriented interventions enhance early disease detection, improve risk communication, strengthen environmental monitoring, and support more resilient public health responses through cross-sector collaboration. The results also demonstrate that institutional coordination, data integration, and shared governance structures are decisive factors in translating One Health principles into measurable health outcomes. Conclusion. The study concludes that the One Health approach represents a transformative paradigm for public and environmental health governance, offering a robust pathway to manage systemic risks at the human–animal–environment interface. Strengthening policy alignment, interdisciplinary capacity, and institutional commitment is essential to realize its full potential.